Observations of NO in the upper mesosphere and lower thermosphere during ECOMA 2010 - J. Hedin; M. Rapp; M. Khaplanov; J. Stegman; G. Witt (Annales Geophysicae, 2012)
In December 2010 the last campaign of the German-Norwegian sounding rocket project ECOMA (Existence and Charge state Of Meteoric smoke particles in the middle Atmosphere) was conducted from Andøya Rocket Range in northern Norway (69° N, 16° E) in connection with the Geminid meteor shower. The main instrument on board the rocket payloads was the ECOMA detector for studying meteoric smoke particles (MSPs) by active photoionization and subsequent detection of the produced charges (particles and photoelectrons). In addition to photoionizing MSPs, the energy of the emitted photons from the ECOMA flash-lamp is high enough to also photoionize nitric oxide (NO). Thus, around the peak of the NO layer, at and above the main MSP layer, photoelectrons produced by the photoionization of NO are expected to contribute to, or even dominate above the main MSP-layer, the total measured photoelectron current. Among the other instruments on board was a set of two photometers to study the O 2 ( b 1 Σ g + − X 3 Σ g ) Atmospheric band and NO 2 continuum nightglow emissions. In the absence of auroral emissions, these two nightglow features can be used together to infer NO number densities. This will provide a way to quantify the contribution of NO photoelectrons to the photoelectron current measured by the ECOMA instrument and, above the MSP layer, a simultaneous measurement of NO with two different and independent techniques. This work is still on-going due to the uncertainties, especially in the effort to quantitatively infer NO densities from the ECOMA photoelectron current, and the lack of simultaneous measurements of temperature and density for the photometric study. In this paper we describe these two techniques to infer NO densities and discuss the uncertainties. The peak NO number density inferred from the two photometers on ascent was 3.9 × 10 8 cm −3 at an altitude of about 99 km, while the concentration inferred from the ECOMA photoelectron measurement at this altitude was a factor of 5 smaller.